Economic Growth, Renewable Energy Consumption, and Health Outcomes in Bangladesh: An Analysis Using Canonical Cointegrating Regression (CCR) - Imran, Khalid; Khanam, Fahima; Habib, Ahsan; Hossain, Md Saddam; Hasan, Mehedi; Haque, Md Obidul (South Asian Journal of Social Sciences and Humanities, 2025)
The global transition to renewable energy is critical for addressing climate change, ensuring  energy security, and improving public health outcomes. However, in developing countries like  Bangladesh, the adoption of renewable energy remains limited despite rapid economic growth  and improvements in life expectancy. This study investigates the long-term relationships  between life expectancy (LE), economic growth (PGDP), and renewable energy consumption  (REC) in Bangladesh, aiming to bridge gaps in understanding the driving force for the adoption  of renewable energy in a developing country context. Using the Canonical Cointegrating  Regression (CCR) method, the study analyzes data from 1991 to 2022, accounting for non stationarity and long-run dependencies. The results reveal that a 1% increase in economic  growth leads to a 0.169% rise in renewable energy consumption, while a 1-year increase in life  expectancy results in a 5.059% increase in renewable energy adoption. These outcomes emphasize the importance of integrating economic and health policies to promote renewable  energy adoption. The study concludes with actionable policy recommendations, including  incentivizing renewable energy investments, enhancing public awareness, and strengthening  policy frameworks to accelerate Bangladesh’s energy transition. This study provides a  contribution to the growing literature on renewable energy adoption in developing countries  and provides critical insights for policymakers, energy providers, and environmental  organizations.
Keywords: Economic growth; renewable energy consumption; health outcomes; Bangladesh; Canonical Cointegrating Regression (CCR); sustainable development